Enhancing Environmental Conservation in Higher Education using Place-based Pedagogy - Ilhami, M. Ridha; Abbas, Ersis Warmansyah; Subiyakto, Bambang; Mutiani, Mutiani; Saliman; Amalia Rezeki (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
The lack of contextual and environmentally relevant learning approaches, such as place-based pedagogy, causes students to lack understanding of the importance of environmental conservation in real life. This article examines the place-based pedagogy approach in increasing students' awareness and participation in environmental conservation, focusing on the habitat of the Proboscis Monkey. The study used qualitative methods to evaluate the impact of an educational approach that connects learning to the local geographic, cultural, and ecological context. Data were collected through observation, interviews, and documentation, involving students, lecturers, and the Indonesian Proboscis Monkey Friends Foundation. Data analysis was conducted thematically with triangulation to ensure validity. The results showed that the place-based pedagogy approach significantly increased students' ecological awareness, encouraged direct involvement in conservation, and built emotional connections with the local environment. The study recommends the integration of the place-based approach into the higher education curriculum, with a focus on practical activities such as field research, community service projects, and seminars with conservation practitioners. In conclusion, the place-based pedagogy approach can effectively increase students' awareness and involvement in environmental conservation. The implications of this research include the need to strengthen collaboration between universities and local communities, develop inclusive and contextual education policies.